Hubungan Kebiasaan Olahraga Dengan Kejadian Osteoporosis Pada Lansia Di Posyandu Lansia Desa Kemantren Kecamatan Tulangan Kabupaten Sidoarjo - Muhith, Abdul; Anam, Mochammad Saiful (SEKOLAH TINGGI KESEHATAN MAJAPAHIT MOJOKERTO, 2015)
The purpose of this study is to determine the relationship of exercise habits to the incidence of osteoporosis in the elderly. This research uses analytic design with cross sectional correlation. Entire elderly population in the Kemantren Village Tulangan district of Reinforcement Sidoarjo regency as many as 154 people to obtain a total of 32 samples were taken by purposive sampling. The results showed that from the 32 respondents who had enough exercise frequency are 16 respondents who are subjected to the risk of osteoporosis occurrence were as many as 13 respondent (40,625%) and low risk as much as 3 respondents (9,375%). While from 10 respondent (31,25%) who are well known of doing exercise, 5 respondents did kind of exercise walking. Data were analyzed using Spearman rank statistical test using SPSS version 16.0 and was obtained p (0,00) < ð¼ð¼ (0,05), so HÎ¿ is rejected it means there is a connection with the exercise habits incidence of osteoporosis in the elderly in the village of IHC Elderly in Kemantren village Tulangan District of Sidoarjo. Exercise habits which are not done regularly and correctly movements will be easy to have symptoms of osteoporosis. Not only the exercise habits but also the gender of elderly will affect the incidence of osteoporosis. Elderly is expected to increase physical activity is good and right in order to get the ideal body.Keywords : exercise habist, osteoporosis, an elderly